Satellite Derived Global Ocean Product Validation/Evaluation - Son, SeungHyun; Platt, Trevor; Sathyendranath, Shubha (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Ocean satellite remote sensing plays important roles in the observations of physical, biological and biogeochemical features in inland, coastal, and global ocean waters, with high temporal and spatial resolution. The satellite-measured ocean products are used for near-real-time ocean monitoring and climate data records to understand short-/long-term variabilities in marine environments and ecosystems as well as for decision making tools to manage social, economic, and environmental benefits. Validation/evaluation including a combination of field measurements and inter-satellite comparison is an essential step in providing more accurate satellite-derived ocean products. In this Special Issue, 14 papers have been published and include research on validation/evaluation, retrieval algorithms of ocean geophysical and biogeochemical parameters, and application of the satellite ocean products in the regional and global ocean. Subjects treated include: Sea Surface Temperature; Sea Ice Surface Temperature from VIIRS thermal infrared sensor; Sea Ice Detection from Spectroradiometer; Sea Surface Winds from HY-2A Scatterometer and GNSS-Reflectometry; Wave Height from Sentinel-3A SAR; Retrievals of Sea Surface Salinity, Chlorophyll-a, Particulate Organic Carbon, Particulate Backscattering, Marine Fishery resource, and Submesoscale Eddies from multiple Ocean Colour sensors.